Electrochemical studies on localised aluminium corrosion and its inhibition : novel approaches to old problems - Liu, Tie (2008)
This thesis mainly concerns the development and application of a novel electrochemical method, based on the combined use of the wire beam electrode (WBE) and scanning reference electrode technique (SRET), for the study of localised corrosion of aluminium (AA1100) and aluminium alloy (AA2024-T3) and its inhibition.